2013
DOI: 10.1103/physrevb.87.165403
|View full text |Cite
|
Sign up to set email alerts
|

Second layer of H2and D2adsorbed on graphene

Abstract: We report diffusion Monte Carlo calculations on the phase diagrams of para-H 2 and ortho-D 2 adsorbed on top of a first layer of the same substances on graphene. We found that the ground state of the second layer is a triangular incommensurate solid for both isotopes. The densities for promotion to a second layer and for the onset of a two-dimensional solid on that second layer compare favorably with available experimental data in both cases.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
4
1
Order By: Relevance
“…2 (the actual determination of the coexistence coverage was not pursued here). A result of our simulation that is in clear quantitative disagreement with existing theoretical predictions [29] and experimental observation [31], has to do with the coverage at which promotion of molecules to the second layer should begin, namely at approximately 0.094Å −2 for a film adsorbed on a graphite substrate (essentially the same value is predicted on graphene [46]). It is worth noting that this is a considerably lower coverage than that at which second layer promotion is observed experimentally [7] and predicted theoretically [12] for a 4 He monolayer film adsorbed on graphite (or graphene [14]).…”
Section: Model and Methodologycontrasting
confidence: 68%
See 1 more Smart Citation
“…2 (the actual determination of the coexistence coverage was not pursued here). A result of our simulation that is in clear quantitative disagreement with existing theoretical predictions [29] and experimental observation [31], has to do with the coverage at which promotion of molecules to the second layer should begin, namely at approximately 0.094Å −2 for a film adsorbed on a graphite substrate (essentially the same value is predicted on graphene [46]). It is worth noting that this is a considerably lower coverage than that at which second layer promotion is observed experimentally [7] and predicted theoretically [12] for a 4 He monolayer film adsorbed on graphite (or graphene [14]).…”
Section: Model and Methodologycontrasting
confidence: 68%
“…The prediction of a second layer promotion coverage carried out in Ref. 46 is based on a comparison of energy estimates arrived at in a DMC projection based on different trial wave functions, and could be affected by the same convergence problems pointed out here. On the other hand, the calculation carried out in Ref.…”
Section: Discussionmentioning
confidence: 96%
“…The present PES has been obtained under the assumption of a pseudoatom behavior for the molecular hydrogen. This is, on the other hand, the usual procedure followed in previous investigations on similar systems formed by H 2 on either molecules or surfaces 22,23,29,33,80,81 . Thus, for example, Špirko et al 29 neglected internal rotations of absorbed molecular hydrogen keeping an equilibrium orientation with a frozen H-H distance, and Nho et al assumed H 2 as spherical particles interacting via a semiempirical Silvera and Goldman potential 81 .…”
Section: Discussionmentioning
confidence: 99%
“…Physisorption on PAHs can be directly considered, on the other hand, as a model to study hydrogen storage 16,17 . The characterization of phase diagrams and the heat capacity of systems formed by layers of H 2 on either graphite or graphene has been the goal of numerous investigations in the [18][19][20][21][22][23][24][25] . Attachment of H 2 and D 2 to fullerenes has been also experimentally investigated in comparison with some other physisorbed species such as rare gases (RG) or N 2 : The electronic absorption spectra recorded by Holt et al 26 revealed a marked influence of the corresponding ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Since we considered a full corrugated substrate, we have to sum up all the C-H 2 interactions, represented by V ext (x i , y i , z i ). The functional form of the C-H 2 potential 36 was the same as in a previous work for the same system on graphene 37 . The carbon atoms were located in the graphite crystallographic positions in the standard way, positions that were kept fixed.…”
Section: Methodsmentioning
confidence: 99%